The hemodynamic effect of eccentricity in visceral branched aneurysms with multilayer stents. (August 2022) - Wang, Guanshi; Li, Zhongyou; Chen, Chong; Yan, Fei; Wei, Junru; Zhang, Zhuo; Chen, Yu
It is preliminarily acknowledged that multilayer stent (MS) is a promising alternative technology in the treatment of visceral branched aneurysms, but hemodynamic consequences of eccentricity in such aneurysms with MS are less examined. In this work, we performed a time-dependent simulation of branched aneurysms of various eccentricities with different stent layers, and thrombosis-related parameters, such as time-averaged wall shear stress (TAWSS), oscillating shear index (OSI), and relative residence time (RRT), were also analyzed. Our results revealed that MS can generally restore laminar flow inside the stent, and allow proper perfusion to vital organs while also fostering a relatively secluded hemodynamic environment for thrombosis formation. Particularly, a flow in the aneurysm sac communicating between the main artery and side branch forms at early systole. However, MS fails to completely eliminate detrimental flow impingement after peak systole, which may hinder aneurysm recovery, especially in the cases of eccentric aneurysms. Therefore, saccular aneurysms should be treated with more caution than fusiform aneurysms. And further therapeutic attempts to keep both perfusion in the proximal region of the aneurysm and isolation in the distal region of the aneurysm should be considered.